Impact of pranayama and vedic mathematics on math anxiety and cognitive skills - Vasant Venkatraman Shastri; Alex Hankey; Bhawna Sharma; Sanjib Patra (Wolters Kluwer Medknow Publications, 2017)
Context: Many children have low self-confidence in mathematics, leading to math anxiety, disturbed cognitive skills, and reduction of the quality of their educational experience. Aims: This study aimed to compare methods of reducing such anxiety and improving cognitive skills using pranayama; and second, introducing pattern recognition in problem solving, using methods of Vedic Mathematics. These methods were chosen because pranayamas are well-established, standardized means of anxiety reduction for any stressful condition, offering a precise standard for comparison, while, Vedic Mathematics shortens and facilitates calculations. Settings and Design: The study design was a randomized controlled trial with three groups: Yoga pranayama (YP), Vedic Mathematics (VM), and controls (CG) taking 12th grade students from a private preuniversity college in India. Method: Intervention was 15 days each of 30 min daily instruction in either selected YP or VM for the two experimental groups. All the three groups received conventional math training every day. Exclusion criteria were major psychological problems. Assessments used the Mathematics Anxiety Rating Scale Revised and Children's Cognitive Assessment Questionnaire. Statistical Analysis Used: SPSS 19.0 was used for statistical analysis. Results: The experimental groups improved on all subscales of both tests, p < 0.001: the VM group improving more on the first test and the pranayama group performing better on the second test. Controls showed no improvements. Conclusion: Introducing pranayama and VM methods as teaching aids would improve cognitive skills and reduce math anxiety and offer a means to improve examination results, as later demonstrated.